Memorandum of understanding between Universiti Teknologi MARA and Sunway University Sdn Bhd / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2019)
UiTM and Sunway University will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.